Laparoscopic Posterolateral Rectopexy for the Treatment of Patients With a Full Thickness Rectal Prolapse: Experience With 63 Patients and Short-term Outcomes - Keehoon Hyun; Shi-Jun Yang; Ki-Yun Lim; Jong-Kyun Lee; Seo-Gue Yoon (Annals of Coloproctology, 2018)
Purpose Although numerous procedures have been proposed for the treatment of patients with a rectal prolapse, the most effective operation has not yet been established. Minimal rectal mobilization can prevent constipation; however, it is associated with increased recurrence rates. We describe our novel method for a laparoscopic posterolateral rectopexy, which includes rectal mobilization with a posterior-right unilateral dissection, suture fixation to the sacral promontory with a polypropylene mesh (Optilene), and a mesorectal fascia propria that is as wide as possible. The present report describes our novel method and assesses the short-term outcomes of patients. Methods Between June 2014 and June 2017, 63 patients (28 males and 35 females) with a full-thickness rectal prolapse underwent a laparoscopic posterolateral (LPL) rectopexy. We retrospectively analyzed the clinical characteristics and postoperative complications in those patients. The outcome of surgery was determined by evaluating the answers on fecal incontinence questionnaires, the results of anal manometry preoperatively and 3 months postoperatively, the patients’ satisfaction scores (0–10), and the occurrence of constipation. Results No recurrence was reported during follow-up (3.26 months), and 3 patients reported postoperative complications (wound infection, postoperative sepsis, which was successfully treated with conservative management, and retrograde ejaculation). Compared to the preoperative baseline, fecal incontinence at three months postoperatively showed an overall improvement. The mean patient satisfaction score was 9.55 ± 0.10, and 8 patients complained of persistent constipation. Conclusion LPL rectopexy is a safe, effective method showing good functional outcomes by providing firm, solid fixation for patients with a full-thickness rectal prolapse.